2020
DOI: 10.1145/3428080
|View full text |Cite
|
Sign up to set email alerts
|

Pricing-aware Real-time Charging Scheduling and Charging Station Expansion for Large-scale Electric Buses

Abstract: We are witnessing a rapid growth of electrified vehicles due to the ever-increasing concerns on urban air quality and energy security. Compared to other types of electric vehicles, electric buses have not yet been prevailingly adopted worldwide due to their high owning and operating costs, long charging time, and the uneven spatial distribution of charging facilities. Moreover, the highly dynamic environment factors such as unpredictable traffic congestion, different passenger demands, and even the changing we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Similar results were found in [77][78][79][80]. Wang et al [81] proposed a pricing-aware real-time charging scheduling system and managed to reduce the charging cost by 24% and the electricity usage by 13%. Arif et al [82] integrated an energy storage system (ESS) and a PV system in a bus depot to reduce charging cost and the peak load on the grid, while Raab et al [83] developed a charging strategy for a BEB depot integrated in the energy management of a virtual power plant operator.…”
Section: Charging Managementsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar results were found in [77][78][79][80]. Wang et al [81] proposed a pricing-aware real-time charging scheduling system and managed to reduce the charging cost by 24% and the electricity usage by 13%. Arif et al [82] integrated an energy storage system (ESS) and a PV system in a bus depot to reduce charging cost and the peak load on the grid, while Raab et al [83] developed a charging strategy for a BEB depot integrated in the energy management of a virtual power plant operator.…”
Section: Charging Managementsupporting
confidence: 67%
“…As a result, offline strategies will not be able to give a reliable charging scheme. Until now, only the authors of [81] paid attention to real-time charging scheduling, so further research is required.…”
Section: Real-time and Multi-objective Charging Management Strategiesmentioning
confidence: 99%
“…Their results revealed that the model could ensure the optimal deployment of facilities for electric bus systems. Based on factors such as the traffic conditions, passenger demand, and weather, which can significantly affect the charging efficiency of electric buses, Wang [24] designed a real-time bus charging scheduling system based on the Markov decision process to analyze charging and operating costs, and it could significantly reduce the charging costs and electricity consumption of buses. In addition to addressing stochastic issues such as ridership and weather, Esmaeilnejad [25] optimized the passenger waiting times and operational costs of bus routes.…”
Section: Cost Analysis Researchmentioning
confidence: 99%
“…Regarding the simulation method, Markov decision process is introduced to describe the charging events (Wang et al 2020). The average reward reinforcement learning method is implemented for problem-solving (Chen and Liang 2020).…”
Section: Problem Descriptionmentioning
confidence: 99%